(untitled) (Iraqi Journal of Medical Sciences, 2009)
Background: Diastematomyelia is the term used to describe the malformation in which the spinal cord is split into two hemi cords, by a bony or cartilaginous ridge, each has a single set of dorsal and ventral nerve roots and is contained within its own dural sheath. On the other hand, diplomyelia indicates that the two spinal cord segments are completely duplicated; four sets of dorsal and ventral nerve roots are present within a single dural sleeve. Objective: To study the clinical, radiological and pathological patterns of diastematomyelia in Iraq, and to emphasize the importance of thorough radiological investigations in order to achieve adequate surgical treatment. Methods: Five patients of proved diastematomyelia were studied retrospectively regarding age, sex, and clinical and radiological features. Four of them were treated surgically by removal of the ridge and release of the tethered cord. Results: The patients were two male and three females. Four of them were below one year of age. Back deformity was the main presenting feature in the first few months of life, while delayed walking was the main presentation after one year of age. The commonest pathological findings were split cord with bony ridge associated with lipoma. CT and MRI provided excellent anatomical and pathological details. Two of the patients developed CSF leak following surgery and had to be reopened. All children made good recovery. Conclusion: Closed spinal midline developmental defect occurs more readily in girls than in boys. Multiple and complex abnormalities are observed: diastematomyelia, diplomyelia, and vertebral malformations. There are three groups of structures involved in the pathological process, skin, bone and neural tissues. CT and MRI provide excellent radiological diagnosis, and should obviate the need for myelography in this group of patients. Surgical treatment is the only way to correct the multiple deformities and defects, and to release cord tethering. Key words: Diastematomyelia, Diplomyelia, Split cord malformation (SCM), Tethered cord syndrome, Bony cartilagenous spur, Fibro cartilagenous spur, Lipoma, Meningomyelocele. Iraqi J Med Sci, 2004; Vol. 3 (1): 62-67